Pengaruh Model Pembelajaran Inside Outside Circle Terhadap Hasil Belajar Ips Siswa Kelas IV di SDN 16 Air Batumbuk - Nurhidayati; Firman; Desyandri (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to see the effect of the model inside the outer circle on student social studies learning outcomes in grade IV SDN 16 Air Batumbuk. This type of research is an experimental study with a population of all fourth grade students of SDN 16 Batumbuk Udara, Solok Regency, which has 32 students. To determine the experimental class and the control class was carried out by random sampling technique or random sampling, which was designated as class IV A as the experimental class and class IV B as the control class. The final test results show that the social science average score of class IVA students is 78.6 for the experimental class and 68.6 for the control class. With the statistical test (a = 0.05) obtained tcount = 2.54 and ttable = 2.04, in other words tcount> ttable, then the H1 hypothesis is accepted, meaning that there is an effect of the learning model inside the outer circle on the learning outcomes of fourth grade students. in social studies subjects